find the general solution of 2tanx - cotx + 1=0
Answers
Answered by
0
2tan x - cot x + 1 = 0
2tan x - 1/tan x + 1 = 0
2tan2x - 1 + tan x = 0
2tan2x + tan x - 1 = 0
2tan2x + 2tan x - tan x - 1 = 0
2tan x(tan x + 1) - 1 (tan x + 1) = 0
(tan x + 1)(2tan x - 1) = 0
tan x + 1 = 0 or 2tan x - 1 = 0
tan x = -1 or tan x = 1/2
x = 3π/4, 7π/4 or x = 3.6052, 0.4636
I think it is the right answer.
2tan x - 1/tan x + 1 = 0
2tan2x - 1 + tan x = 0
2tan2x + tan x - 1 = 0
2tan2x + 2tan x - tan x - 1 = 0
2tan x(tan x + 1) - 1 (tan x + 1) = 0
(tan x + 1)(2tan x - 1) = 0
tan x + 1 = 0 or 2tan x - 1 = 0
tan x = -1 or tan x = 1/2
x = 3π/4, 7π/4 or x = 3.6052, 0.4636
I think it is the right answer.
Similar questions